“El material lúdico en el desarrollo de la lectoescritura en los estudiantes de tercer año de educación general básica de la unidad educativa comunitaria intercultural bilingüe "Surupucyu", del cantón Guaranda, provincia Bolívar, durante el año 2022” - Manobanda Guaman, Mercedes Marianela (2022)
The present curricular integration work was carried out due to the need to analyze the current situation of playful materials in the development of literacy in children of the third year of Basic General Education of the UECIB Surupucyu, and to achieve this, a work was carried out research with a mixed approach in order to investigate in depth the object of study through the teacher and the observation of the students. In this way, the influence of the playful material in the development of literacy in the apprentices was determined, both the teacher and the students expressed their agreement with the use of playful resources in the educational process because it motivates them to learn and improve their knowledge of a dynamic way, where the game takes the main role in the construction of significant knowledge. Finally, as a result of the investigation and the contribution of the authors of the project, a pedagogical guide was designed for the construction and execution of 3 recreational activities, considering the presence of the Kichwa mother tongue and the Castilian intercultural language in the educational unit.